ANALISIS MANFAAT ASESMEN DIAGNOSTIK PADA SISWA SEKOLAH DASAR - khulaifi, azis (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research aims to look at the implications and benefits of initial diagnostic assessments in learning, especially at the elementary school level. Assessment is a series of assessments to determine student progress. Diagnostic assessment is a series of assessments in the independent curriculum which aims to identify characteristics, competency conditions, strengths, weaknesses and student learning models. The diagnostic assessment aims to see the initial abilities possessed by students both cognitively and non-cognitively, so that the learning process can be seen and mapped according to the competencies and abilities possessed by the students. Diagnostic assessments have become known and implemented in Indonesia since the implementation of the independent curriculum. The independent curriculum provides opportunities for students to develop more competencies, skills and character without placing demands on learning. The independent curriculum was born after the Covid-19 outbreak. In 2022 the independent curriculum will begin to be implemented in Indonesia in some schools and will begin to be implemented nationally in the new academic year 2024. The aim of the independent curriculum is to catch up with various post-Covid lags and answer the challenges of current developments. It is hoped that the independent curriculum can improve the quality of Indonesia's human resources according to current developments.